Healing Garden as a Green Open Space in Hospital - Lestari, Marselli Widya; Favurita, Anisgupta Larasaty (Jurnal Medis Islam Internasional, 2024)
Introduction: Natural environments within healthcare settings have received growing interest for their potential role in supporting health and well-being. Healing gardens are typically green open spaces within hospitals that promote the physical, mental, and emotional rehabilitation of patients, also benefiting the staff and visitors. This paper presents a narrative review pertaining to the theoretical underpinnings, history, and empirical research on the effectiveness of healing gardens in health care settings. Result: It has been reviewed in recent literature that healing gardens have a huge effect on stress reduction, mood enhancement, improved cognitive functioning, and accelerated physical recovery. Some key design principles, such as access, sensory stimulus, and restorative components, arebanner in maximizing this potential therapy. Healing gardens, therefore, become one of the most cost-effective ways for patient care and staff well-being; however, there might be some little challenges in implementing and maintaining them. Conclusion: Future research should be directed toward long-term impacts and design innovations that ensure maximum efficacy of these therapeutic spaces. Future work into the healing garden would focus on developing more patient-centered, restorative, and sustainable healing environments that underscore this deep connection between nature and health.